Analisis Cemaran Bakteri Coliform dan Escherichia coli pada Sampel Sari Tebu yang dijual di Pedagang Kaki Lima - Toberni S Situmorang; Helen Anjelina Simanjuntak; Rahmiati Rahmiati (Herbal Medicine Journal, 2026)
Sugarcane juice is a beverage extracted from sugarcane that is popular and widely consumed by the public. This condition creates business opportunities, particularly for street vendors. However, processing practices that do not adequately consider hygiene and sanitation aspects can increase the risk of contamination by pathogenic bacteria, especially Coliform bacteria and Escherichia coli. This study aimed to determine the level of contamination of Coliform bacteria and Escherichia coli in sugarcane juice sold by street vendors. This research employed a descriptive qualitative design using the spread plate isolation method. Samples were obtained from five street vendors located along the main roads of Tanjung Selamat Subdistrict, Medan Tuntungan District, Medan City. Bacterial contamination testing was conducted using the Most Probable Number (MPN) method, which consisted of three stages: presumptive test, confirmatory test, and completed test. The results showed that one out of five sugarcane juice samples tested were detected to contain Coliform bacteria and Escherichia coli. These findings indicate that one sugarcane juice samples sold by street vendors did not meet food safety standards and may pose potential health risks to consumers. Therefore, improved implementation of hygiene and sanitation practices in the processing and serving of sugarcane juice is necessary.